(3Jhbja GdMcGe, Ydi ZhGeV GdCMcGes - (3GdTGaYj, GdCbagSj, GdbGgQj, CHh GdYHGS, TgGH GdOjf, CMeO Hf YeGO Hf jhSa Hf YHO GdfHj, J (B808(3g`s
(3ChdgG (B:s
(3HSe Gddg(B...(3hLYd GdfGS TYhHG(B...(3hHWhfG hCaNGPG hLYd dcd TjA bOQG, aGdTYH cGdQCS hGdbHjdI cGdjO (B...(3hgj GdJj jChj EdjgG GdQLd hJchf dg SJQG(B...s
(3BNQgG (B:s
(3hGdJhHI fhYGf JhHI ef Gddg JYGdi Ydi GdYHO, hJhHI ef GdYHO Edi Gddg JYGdi aJhHI Gddg JYGdi Ydi GdYHO Cf jHZV dg GdeYGUj hjMHH Edjg GdWGYGJ (B...(3Gddge JH YdjfG Efc CfJ GdJhGH GdQMje (B...(3fLR Jhbja GdMcGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B1(3,U(B184s
(3cTa GdXfhf(B:(3L(B1(3,U(B508s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3Gdabg GdTGaYjs